Law and the restoration / 2nd volume Law and Latter-Day Saint thought and scripture - Oman, Nathan (Law and the restoration, 2024)
"Law and the Restoration: Law and Latter-day Saint thought and scripture is a comprehensive exploration of the intricate relationship between legal principles and the doctrines of The Church of Jesus Christ of Latter-day Saints. Author Nathan B. Oman delves into the profound ways in which Mormon theology intersects with legal concepts, offering readers a detailed analysis of church doctrines, their authority, and their implications for members' daily lives. In doing so, Oman addresses foundational questions about the nature of church authority, the role of personal judgment, and the dynamic interplay between divine law and secular legal systems. The book is not just an academic treatise but a thoughtful discourse aimed at elucidating how Mormons navigate complex moral and legal landscapes in their quest to reconcile faith with modern societal norms. Each chapter serves as a deep dive into specific aspects of Mormon doctrine and its legal ramifications. From the examination of Nephi's actions in the Book of Mormon to the contemporary debates surrounding same-sex marriage and civil disobedience, Oman provides a balanced and respectful analysis that seeks to understand rather than critique. This book is an invaluable resource for scholars, legal practitioners, and anyone interested in the intersection of religion and law, providing a rich narrative that underscores the ongoing dialogue between faith and jurisprudence within the Latter-day Saint tradition."--